Gender Perspective: Independent Learning of Generation Z in Online Learning - Muhtadi, Ali; Ismaniati, Christina; Haryanto, Haryanto; Miyarso, Estu; Jayanti, Desi Dwi (Universitas Pendidikan Ganesha, 2022)
Independence in learning is a prerequisite for the implementation of basic online learning which is still a problem in itself, especially among the Z generation whether it is male or female, even though gender is one of the influencing factors in the process of developing learning independence. This study aims to analyze the learning independence of Generation Z in participating in online learning based on gender. This type of research is descriptive quantitative. The population is students across study programs and faculties with a total sample of 70 students consisting of 35 male students and 35 female students. The sample was taken using the snowball sampling technique. Collecting data using online survey techniques with online questionnaire instruments (google form) scale 5. The data were analyzed using quantitative descriptive techniques in the form of percentages. Based on the research, it shows that the mean score of learning independence for male students is 3.74, while female students are 3.84 with a significant difference value of 0.031. From these data it can be concluded that there are differences in the learning independence of Generation Z in terms of gender, this can be seen from the aspects of indicators of self-confidence, disciplined behavior, attitude of responsibility, initiative attitude and self-control attitude possessed by both sexes during follow online learning. The implication of this research is that generation Z becomes able to evaluate themselves about the picture of their learning independence.